Architecting Blockchain Solutions - Holbrook, Joseph (Cisco Press, 2018)
6 Hours of Video Instruction Description Quickly gain a deep understanding of blockchain technology to drive revenue in your organization. Overview Architecting Blockchain Solutions LiveLessons covers blockchain basics, ledgers, and several use-case scenarios in detail. Learn the main technologies for supporting blockchain use cases and how these technologies work with other technologies. Joe Holbrook discusses use cases that cover financial, insurance, science, technology, and other industries that enable you to gain a full grasp of blockchain capabilities. This course starts out by covering blockchain fundamentals, including how a blockchain compares to traditional infrastructure and how Ethereum is used as a blockchain platform. It then discusses the important factors of blockchain architectures for which every organization should have a concise understanding, including blockchain nodes, blockchain networking, and layers. Holbrook demonstrates options for running blockchain on the various public cloud providers, including AWS, GCP, Azure, and IBM, and details numerous blockchain business models and best practices for software lifecycles. He covers significant blockchain development and planning as well as several blockchain development challenges. The course finishes with a discussion of providing blockchain solutions based on customer requirements. Topics include Lesson 1: Blockchain Basics Lesson 2: Understanding Ethereum Lesson 3: Blockchain Platform Architectures Lesson 4: Blockchain Business Models Lesson 5: Defining Business Models (B2B) Lesson 6: Defining Business Models (B2C) Lesson 7: Defining Business Models (G2C) Lesson 8: Blockchain Costing Lesson 9: Blockchain Solution Development Lesson 10: Blockchain Design Best Practices Lesson 11: SDLC Lesson 12: Building the Blockchain Lesson 13: Blockchain Pre-Sales Cycle Lesson 14: Blockchain Demand About the Instructor Joe Holbrook has been in the IT field since 1993, when he was exposed to several HPUX systems on board a U.S. Navy flagship. He has migrated from the UNIX world to storage area networking (SAN), enterprise virtualization, and cloud architectures, and now specializes in blockchain and cryptocurrency. He previously worked for numerous companies such as HDS, 3PAR, Brocade, HP, EMC, Northrup Grumman, ViON, Ibasis.net, Chematch.com, SAIC, and Siemens Nixdorf. Currently he works as a subject matter expert specializing in enterprise cloud and blockchain technologies. He is the o ...